Prediction of Lactation Milk Yield from Part Yield in Jaffarabadi Buffalo - Chaudhari, Pravin N.; Gadariya, Mahesh R.; Kapadiya, Pratik S.; Gamit, Pranav M.; Savaliya, Bhagavanji D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An attempt was made to predict standard lactation milk yield (SLMY) by simple regression equation from weekly, fortnightly andmonthly, individual and cumulative part yield in Jaffarabadi buffalo. A total of 176 normal lactations of Jaffarabadi buffaloes from 1stto 6th parity with lactation length >210 days were analysed. Correlation coefficients between 305-days milk yield (SLMY) and differentweekly (1st to 20th week), fortnightly (1st to 5th fortnight) and monthly (1st to 5th month), individual and cumulative part lactations werepositive and significant (P
Keywords: Cumulative yield; Jaffarabadi buffalo, Lactation milk yield; Part yield; Prediction